Selected Lectures of the Conference “New Approaches and Technologies – From Fetus to Adult”; Cagliari (Italy); October 25, 2025 - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2025)
Selected Lectures of the Conference “New Approaches and Technologies – From Fetus to Adult”; Cagliari (Italy); October 25th, 2025 The Conference “New Approaches and Technologies – From Fetus to Adult” is a Satellite Meeting of the 21st International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 22nd-25th, 2025. LECT 1. NEW ASSISTED REPRODUCTIVE TECHNOLOGY (ART) TECHNIQUES TO INCREASE THE BIRTH RATE IN SARDINIA: MEDICAL-SOCIAL FREEZING AND HETEROLOGOUS FERTILIZATION • G. Monni (Cagliari, Italy) LECT 2. RENAL REGENERATIVE MEDICINE: WHAT DID WE LEARN? • G. Faa, V. Fanos (Cagliari, Italy) LECT 3. TRANSLATIONAL POTENTIAL OF ESSENTIAL OILS AND NANOCARRIERS IN ANTIMICROBIAL THERAPY: NOVEL STRATEGIES FROM FETAL TO ADULT LIFE • F. Mondello, M. Di Vito, M.L. Ricci (Rome, Italy) LECT 4. THE EUROPEAN LIFE MILCH PROJECT: WHERE DO WE STAND? • P. Palanza, V. Fanos, A.M. Papini, S. Perrone, T. Ghi, S. Paterlini, M.M. Brambilla, D. Baccolo, C. Scopa, A. Ardenghi, A.M. Shulhai, C. Caffarelli, F. Nuti, F. Fernandez, C. Sartori, F. Alberghi, B. Righi, M. Fontana, L. Filonzi, C. Petrolini, B. Piccolo, E. Turco, R. Pintus, C. Piras, S. Petza, A. Dessì, F. Nonnis Marzano, D. Ponzi, A. Pelosi, M.E. Street (Parma, Cagliari, Florence, and Reggio Emilia, Italy) LECT 5. METABOLOMICS AND NUTRITION • S. Alessandri (Rome, Italy) LECT 6. METABOLOMICS IN RHEUMATIC DISEASES • M. Valentini (Faenza, Italy) LECT 7. NEW APPROACHES IN AUTISM MANAGEMENT • M. Greco (Turin, Italy) LECT 8. METABOLIC DETERMINANTS IN FIBROMYALGIA SYNDROME STUDIED WITH THE EPIGENETIC METHOD • B. Pische, A. Scognamillo, G. Terziani, G. Fenu Pintori (Sassari and Brescia, Italy) LECT 9. METABOLOMICS AND MICROBIOMICS IN CLINICAL PRACTICE • C. Marzetti (Bologna, Italy ) LECT 10. THE EPIGENETIC REVOLUTION IN THE AGE OF POLLUTION: INDIVIDUAL RESPONSIBILITY TOWARDS FUTURE GENERATIONS • G. Terziani (Brescia, Italy) LECT 11. ARTIFICIAL INTELLIGENCE: FRIEND OR FOE? • A. Colangelo (Trento, Italy)